“Us” or “Them”: Internal Migrants in the Perceptions of the Siberian Cities’ Citizens (on the Example of Irkutsk, Krasnoyarsk and Tomsk) - Dmitry O. Timoshkin; Fedor A. Smetanin; Diana E. Gorshkova; Andrei A. Voloshin; Kirill A. Ivanov; Iuliia O. Koreshkova; Arina E. Sorokina; Sofiya A. Ignatenko; Galina A. Shaposhnikova-Murashova (Регионология)
Introduction. The study examines the process of civic identity formation in contemporary Russia in relation to the production and crossing of boundaries between “imagined communities”. Most existing research focuses on how cross-border migration influences the host community’s rethinking of its identity. At the same time, internal migrants, being part of the same society, can impact the identification of the “us-group” within the country. Studying this issue is crucial for understanding the configuration and structure of civic identity from the perspective of maintaining and preserving social solidarity. The authors analyze the influence of internal migration on the perceptions of residents in three Siberian cities regarding “us” and “them.” The aim of the study was to identify the mechanisms by which members of the “us-group” construct boundaries with respect to internal migrants, as well as the degree of permeability of these boundaries.